The Generalization of the Comparative Advantage Theory - Leszek Jasiński (Vasyl Stefanyk Precarpathian National University, 2017)
Economic textbooks relate the principle of comparative advantage using examples of two products and two countries, the 2x2 case. We shall suggest an approach describing any finite number of products m and countries n, the mxn case, where m>2, n>2. For this purpose the linear programming will be used.